Review of Studying Social Interactions With the Usage of Eye-Tracking Analysis - N.Ya. Ageev; I.A. Dubovik; G.I. Kalinina; A.V. Konokotin (Психолого-педагогические исследования, 2023)
This article provides an overview of empirical studies focused on the possibilities of using the eye-tracking analysis to study social interactions. The whole text is divided into conceptual blocks, such as eye-tracking as a method of psychological research and its possibilities of studying social interactions. A brief review on the present topic revealed that one of the most relevant objectives in this research area is in line with the studies of the features of multimodal communication carried out simultaneously through several “channels” of information transmission (including visual feedback) with its correlation with the collaborative productivity and organizing of effective forms of joint acitivity. The observed data improve scientific understanding of the mechanisms by which different modes of interaction (joint attanetion, mutual understanding, reflection, communication) arise and are implemented by the main participants of joint activity. It was deliberately stressed that this line of research is needed to be supplemented by the studies on dynamics of oculomotor activity at different stages of joint actions and interactions.